Deskripsi Pemahaman Geometri Siswa SMP pada Materi Segiempat berdasarkan Teori Van Hiele ditinjau dari Gaya Kognitif Siswa - Tahmir, Suradi; Ja'faruddin; Abbas, Nurul Fitriany (Issues in Mathematics Education (IMED), 2018)
This research is a descriptive research with qualitative approach which aims to describe Junior High School students’ geometry understanding on quadrilateral based on van Hiele Theory and observed from students’ cognitive style. Subjects in this study were Junior High School students who were selected based on GEFT test i.e. 1 student who has Field Dependent cognitive style and 1 student who has Field Independent cognitive style. Then, subject undertook a geometry understanding test on quadrilateral material and conducted interviews to obtain data of students’ geometric understanding on quadrilateral. Subjects’ geometry understanding were described by van Hiele theory that contained van Hiele level of geometry understanding i.e. visualization, analysis, abstraction, formal deduction, and rigor. The result of this study show that there are differences in geometry understanding between student with Field Dependent cognitive style and student with Field Independent cognitive style. Student with Field Independent cognitive style has geometry understanding on quadrilateral better at each level of geometry understanding that had been achieved and was at higher level than student with Field Dependent cognitive style. Student with Field Independent cognitive style has reached the initial stage of formal deduction, while student with Field Dependent cogitive style still is at analysis level.